2023
DOI: 10.3389/fpls.2022.1098048
|View full text |Cite
|
Sign up to set email alerts
|

Defense response of strawberry plants against Botrytis cinerea influenced by coriander extract and essential oil

Abstract: Essential oils and extracts are investigated in sustainable plant protection area lately. Alternative antifungal substances are especially relevant for major economic-relevance pathogens, like Botrytis cinerea (causal agent of strawberry grey mold), control. However, the reaction of plants to alternative protection with plant-origin products is currently unknown. Induced stress in plants causes changes in antioxidant and photosynthetic systems. The aim of the research was to determine the defense response of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…There are studies indicating plant extracts' impact on antioxidant activity and compounds in plants and fruits. Coriander seed essential oil and extract decreased DPPH, ABTS antioxidant activity and total phenolic compounds in inoculated strawberry leaves, but only with lower applied concentrations [41]. A dose-dependent effect was observed with Lawsonia inermis L. extract, which increased wheat shoot and root system growth and accumulated 90% more total phenolic compounds in wheat compared to untreated plants [42].…”
Section: Introductionmentioning
confidence: 91%
“…There are studies indicating plant extracts' impact on antioxidant activity and compounds in plants and fruits. Coriander seed essential oil and extract decreased DPPH, ABTS antioxidant activity and total phenolic compounds in inoculated strawberry leaves, but only with lower applied concentrations [41]. A dose-dependent effect was observed with Lawsonia inermis L. extract, which increased wheat shoot and root system growth and accumulated 90% more total phenolic compounds in wheat compared to untreated plants [42].…”
Section: Introductionmentioning
confidence: 91%
“…Research has shown that the enzyme activity of watermelon plants PPO and SOD increased observably after treating the extraction of S. aromaticum, Stellera chamaejasme, and Glycyrrhiza uralensis (Zhang 2019). In addition, induced stress in plants causes changes in antioxidant and photosynthetic systems, Dėnė et al (2023) found that Coriandrum sativum could increase the photosynthetic capacity and antioxidant response of strawberry plants; however, it had a negative effect on the suppression of strawberry grey mould.…”
Section: Reviewmentioning
confidence: 99%
“…Many of these phytochemicals have beneficial effects on human health as well, effectively treating various diseases [ 10 ]. Additionally, extracts obtained from a broad spectrum of plants were proven to have inhibitory effects against horticultural fungal pathogens in vitro [ 11 , 12 , 13 , 14 ]. For example, different extracts of Hyssopus officinalis L. and Salvia officinalis L. were shown to be rich in bioactive compounds, which contribute to the anti-fungal effect [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%